Complication Rates Associated with Transvenous Pacemaker Implantation in Dogs with High‐Grade Atrioventricular Block Performed During versus After Normal Business Hours. (January 2015) - Ward, J.L.; DeFrancesco, T.C.; Tou, S.P.; Atkins, C.E.; Griffith, E.H.; Keene, B.W.
<x xml:space="preserve">Abstract</x> Background Transvenous pacemaker implantation in dogs is associated with a relatively high complication rate. At our institution, pacemaker implantation in dogs with high‐grade atrioventricular block (HG‐AVB) frequently is performed as an after‐hours emergency. Hypothesis Among dogs with HG‐AVB, the rate of major complications is higher when pacemakers are implanted after hours (AH) compared to during business hours (BH). Animals Client‐owned dogs with HG‐AVB that underwent transvenous pacemaker implantation between January 2002 and December 2012 at the North Carolina State University Veterinary Teaching Hospital. Methods Retrospective medical record review. Two‐year follow‐up was required for complications analysis. Results Major complications occurred in 14/79 dogs (18%) and included lead dislodgement, lead or generator infection, lead or generator migration, and pacing failure. Incidence of major complications was significantly higher AH (10/36, 28%) compared to BH (4/43, 9%; P = .041), and all infectious complications occurred AH. Median survival time for all dogs was 27 months and did not differ between AH and BH groups for either all‐cause (P = .70) or cardiac (P = .40) mortality. AH dogs were younger than BH dogs (P = .010), but there were no other clinically relevant differences between BH and AH groups in terms of demographic, clinical, or procedural variables. Conclusions and Clinical Importance At our institution, AH transvenous pacemaker placement is associated with a higher rate of major complications (especially infections) compared to BH placement. This difference may be because of a variety of human factor differences AH versus BH.